Epidemiological, laboratory and treatment characteristics in hemodialysis patients in a high altitude population - Arellán Bravo, Luis Jesus (2022)
Objective. To describe the prevalence of anemia among patients undergoing chronic hemodialysis treatment in an altitude population (3200 m a.s.l.) in the Department of Junín (Peru). Methods. Observational, retrospective study. Data were taken from the National Dialysis Registry (RENDES, 2021) in the Department of Junín (Peru) and from the medical records of hemodialysis patients of the EsSalud Social Security in the year 2021. The sample population consisted of all patients who constituted the Chronic Hemodialysis Program of the Junín Region. Descriptive data were analyzed in Stata, version 17.0. Results. The prevalence of anemia was 3.9%. Only 5 patients had anemia associated with chronic kidney disease (CKD) (3.9%). Data were collected from 128 patients. 64.8% (n = 83) were male. The main cause of CKD was arterial hypertension (AHT) (37.5%), then type 2 diabetes mellitus (24.2%). The mean hemoglobin was 12.8 ± 2.38 g/dL. Mean mean corpuscular volume (MCV) was 95.42 ± 4.9 fl, mean corpuscular hemoglobin (MCH) 32.13± 1.9 pc, and mean corpuscular hemoglobin concentration (MCHC) mean was 33 ± 1.15 g/dL. The average serum iron level was 100 micromol/L and the average ferritin level was 1300 ng/ml. Patients used on average 23000 IU of erythropoietin (EPO) monthly, 400 mg of iron monthly and 4 mg of hydroxocobalamin monthly. Conclusions. Anemia rates in patients with chronic hemodialysis treatment in Huancayo, Junín, in a high altitude city, are low (3.9%).